Características químicas e cristalino-estruturais de ferritas naturais do tipo espinélio de pedossistemas magnéticos representativos, em Minas Gerais - Fernando Dias da Silva (2008)
The present work was dedicated to the characterization of iron oxides, mainly those iso-structural to the spinel, and to the understanding of the main steps of the chemical and crystallographic mechanisms related to the pedogenetic transformations of magnetite (Fe3O4) and magnesioferrite (Fe2MgO4), in three selected pedosystems. Magnetic fractions of rock and soil, from lithologies of steatite (soapstone), tuffite and itabirite were magnetically separated with a hand magnet. The chemical composition of the magnetic fractions, after treatment with a citrate-bicarbonate-dithionite (CBD) mixture, were determined byconventional chemical analysis. The crystallyne structures were established through analysis of powder X-ray diffractron (XRD) data from the synchrotron source (XPD line of the Brazilian Synchrotron Light Laboratory - Campinas, SP, Brazil), Mössbauer spectroscopy andX-ray absorption at near-edge structure (XANES). The crystal-structural analysis of the magnetic fraction of the itabirite rock revealed the occurrence of two mineralogical phases: magnetite and hematite. In the soil magnetic concentrate, besides the phases found in the rock, maghemite was also observed. A significant reduction of the amount of magnetite from the soil, relatively to rock material, was observed. This result suggests that part of the rock magnetite was oxidized to the maghemite. The lattice dimension of the cubic cell of the spinel-ferrites from the tuffite magnetic fraction, as deduced from the Rietveld refinement of the X-ray diffraction data, were: for magnesioferrite a = 0.837563(2) nm; for maghemite a = 0.835758 nm. An overallmodel for the pedogenetic transformation of iron oxides could then be proposed. In pedosystems derived from tuffite, magnesioferrite is transformed to Mg-substituted maghemite: 2 4 x 2-x 3 2 3 MgFe O Mg Fe O Fe O . From 298 K-Mössbauer data for the magnetic fraction of the steatite rock, a magnetite with two populations of iron-sites, separated by slight differences of their hyperfine parameters, with octahedral coordination was identified. The Rietveld structural refinement of the powder XRPD data is consistent with two cubic phases. Below the Verwey temperature, TV 120 K, it can be identified, through the structural refinement, three crystallographic structures: two cubic, with different cell dimensions, and a monoclinic phase. This is the first report of this type of behavior in natural samples, involving the Verwey transition. Corresponding analyses of collected data DRX at T < TV, at 15 K, 50 K and 100 K led to a better characterization of these monoclinic (space group, P2/c) and cubic ( Fd3m ) strucutres. From magnetic fraction of the soil-material derived from this steatite, magnetite and hematite (Fe2O3) were identified. Differently from the rock, the low temperature, T = 15 K, data analysis for the soil-magnetite does not indicate any crystallographic transition.